Comparison effectiveness between cetylpyridinium chloride and triclosan mouthwash on plaque - Chinger, Gurtej Singh; Hadidjah, Dede; Rusminah, Nunung (Padjadjaran Journal of Dentistry, 2012)
Introduction: Dental plaque is a soft deposit that accumulates on the teeth. It is a complex microbial community with as many as 400 distinct bacterial species. One of the most prevalent diseases of the oral cavity is periodontal disease which begins with gingivitis. The main cause of gingivitis is plaque accumulation. Aim of this research is to comparison  effectiveness of mouthwash containing cetylpyridinium chloride and mouthwash containing triclosan on plaque. Methods: The research was experimental study, with the double blinded parallel design. A total of 30 students of SMA Pasundan 8 were chosen. Clinical examination was conducted to obtain the plaque score using the Quigley Hein Index (modified) 1970. Subjects were divided into two groups. One group was given the cetylpyridinium chloride mouthwash and the other group was given triclosan mouthwash. Data were then analysed using the ANOVA test. Results: there is no significant difference between the effectiveness of mouthwash containing cetylpyridinium chloride and mouthwash containing triclosan on plaque (P>0.05). Conclusion: the mouthwash containing cetylpyridinium chloride and mouthwash containing triclosan is effective in reducing plaque.